KAJIAN NILAI, FUNGSI, DAN MAKNA YANG TERKANDUNG DALAM SENI DONGKREK - Hartini Hartini (Premiere Educandum : Jurnal Pendidikan Dasar dan Pembelajaran, 2012)
Dongkrek attraction is a stage which is composed of music, dance and dramatic story arranged in a single set of show. The structure of the stage is seen in the unique type of music instrument. Masks have become the reflection of the characterization of the characters in stage. The music intsruments of Dongkrek attraction are: kenthongan, kenong, bedug, beri, korek and gong pamungkas. The masks are typified as topeng buta/gendruwo; topeng roro perot, topeng roro ayu and topeng eyang palang. Cultural values reflected in Dongkrek attraction consist of those of education, moral, leadership, heroism and aesthetics. Dongkrek attraction can also serve functions of fulfiling psychological needs, expressing self-esttem, releasing tension and ammusement. The masks in Dongkrek represent some characters; topeng buta/gendruwo for evil, eyang palang for wisdom.